Phenology, heat unit requirement and yield of wheat (Triticum aestivum) varieties under different crop-growing environment - PANDEY, I B; PANDEY, R K; DWIVEDI, D K; SINGH, R S (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 4 consecutive winter (rabi) season of 2003 to 2007 to study the phenology, growing degree days and its subsequent effect on grain yield of wheat (Triticum aestivum L.emend. Fiori and Paol) varieties grown under varying environmental conditions. The crop sown on 23 November took maximum calendar days and growing degree days for tiller initiation, boot stage, ear emergence, milk stage, dough stage and maturity which got reduced significantly with subsequent delay in sowing time and recorded lowest value on 4 January-sown crop. Highest heat-use efficiency and grain were also obtained when sowing was done on 23 November, both heat-use efficiency and grain yield decreased significantly on delayed sowing. The reduction in grain yield was recorded to the tune of 7.45, 30.91 and 55% when sowing was delayed on 7 December, 21 December and 4 January, respectively as compared to 23 November-sown crop. Per unit increase in growing degree days over 1477.7°C increased grain yield to the tune of 11.1, 7.2, 5.6 and 5.8 kg/ha/day of wheat varieties ‘K 9107’, ‘PBW 343’, ‘HP 1744’ and ‘NW 1014’, respectively. Among the tested varieties, timely-sown wheat varieties took highest calendar days, growing degree days for these phenophases and recorded highest heat-use efficiency and grain yield than late-sown wheat varieties. The significant reduction in grain yield of timely-sown wheat varieties ‘K 9107’ and ‘PBW 343’ was recorded when sowing was delayed beyond 23 November, while significant reduction in late-sown varieties, ‘HP 1744’ and ‘NW 1014’ was noticed beyond 7 December. The reduction in grain yield of timely-sown varieties was more pronounced beyond 21 December.